Two significant moments in the history of Kaaps - van Rensburg, Christo (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
Two matters are considered in this paper. (i) The identification of the first version of Kaaps, the progenitor of Afrikaans. The earliest version of Kaaps was recorded during the first period of the history of Afrikaans - the period prior to 1652. This period commences with the first visits to the Cape by Dutch mariners. The written records of Kaaps dating from that period are older than any other manifestation of forms in Afrikaans. Some of these early words are currently still in use among speakers of Kaaps, while others have been incorporated into Standard Afrikaans, or appear in dictionaries and the AWS (Afrikaanse Woordelys en Spelreels- Wordlist and Spelling rules for Afrikaans). Some even continue to survive in the spoken Afrikaans of a number of regional dialects. Reference is also made in this chapter to how Kaaps eventually developed and played an important role in the shaping of other varieties of Afrikaans. (ii) The circumstances leading to the incorporation of elements of other varieties into the core description of Afrikaans. In describing Afrikaans, language historians usually ask where particular words and constructions come from. But the question how is actually of greater value when investigating the development of Afrikaans. Ek (I) is a word in Kaaps which was, over time, absorbed into general use in Afrikaans. An analysis of how this process took place reveals that the "how" questions are of greater importance in the history of the language than the "when" and "where" questions. The true story of Afrikaans is a socio-historical one. Destigmatization, and the circumstances leading to changing norms, are evoked by the "how" questions.